1992
DOI: 10.1016/0014-5793(92)81426-m
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of store release from transmembrane influx of calcium in human neutrophils

Abstract: Release of C,t:" from intracc!lular stores wa~ wsuahsed in individual neutrophih m the pre~ence of the Mn '* or SKF 96365. influx of Mw'" quenched rata-2 close to the plabma membrane but did not quench fnra-2 at the s~le of stole release The size and location of the 'cloud' of elewtted Ca:" was unaffected by the channel blocker SKF 96365. Furthe]morc, the ~ze and Ioeatton was unaffected by the ple~ence of extracellular Ca"'. This dhsoe;.'ttion of transmembrane reflux from ~tore release delnonstrates that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The data also further support the hypothesis that cations do not first enter endothelial cells via the internal stores, but by a direct route into the cytoplasm (Putney, 1986(Putney, , 1990. Although our evidence strongly suggests a selectivity of ionomycin for endomembranes [as has previously been only hinted at (Stauderman and Pruss, 1989; Albert and Tashjian, 1986;Neylon and Irvine, 1991)], there are reports of ionophore being unaffected by conditions which can nevertheless blunt the agonist-stimulated Ca2+ entry (McCarthy et al, 1989;Davies et al, 1992;Graier et al, 1992). We cannot fully explain such discrepancies in the light of our data, but suggest that there may be differences in experimental protocols (e.g.…”
Section: Route Of Cation Entrysupporting
confidence: 88%
See 3 more Smart Citations
“…The data also further support the hypothesis that cations do not first enter endothelial cells via the internal stores, but by a direct route into the cytoplasm (Putney, 1986(Putney, , 1990. Although our evidence strongly suggests a selectivity of ionomycin for endomembranes [as has previously been only hinted at (Stauderman and Pruss, 1989; Albert and Tashjian, 1986;Neylon and Irvine, 1991)], there are reports of ionophore being unaffected by conditions which can nevertheless blunt the agonist-stimulated Ca2+ entry (McCarthy et al, 1989;Davies et al, 1992;Graier et al, 1992). We cannot fully explain such discrepancies in the light of our data, but suggest that there may be differences in experimental protocols (e.g.…”
Section: Route Of Cation Entrysupporting
confidence: 88%
“…Furthermore, ionomycin-induced cation entry in human umbilical-vein endothelial cells (HUVEC) may share a common route of entry with histamine-induced entry, since both responses were inhibited by thrombin (Neylon and Irvine, 1991). On the other hand, others have shown that inhibitors of Ca2+ entry such as SK&F 96365 (Davies et al, 1992;Graier et al, 1992) or phorbol ester (McCarthy et al, 1989) had no effect on ionophore responses, while decreasing agonist-driven effects, which is more consistent with the ionophores directly translocating bivalent cations across the plasma membrane.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Taken together these results indicate that [Ca2+]i is controlled in U937 monocytes by mechanisms distinct from those which appear to operate in other myeloid cells, such as neutrophils, stimulated with C5a and formylpeptide. be dependent on the emptying of internal Ca2+ stores (Putney, 1990;Alonso-Torre et al, 1993), although influx does not appear to occur via the organelle which contains the Ca2+ store (Davies et al, 1992). The elevation of [Ca2+]1 in fMLP-stimulated neutrophils appears to be entirely dependent on pertussis-toxinsensitive G-proteins (Goldman et al, 1985).…”
Section: Introductionmentioning
confidence: 99%